2020
DOI: 10.1186/s12917-020-02599-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum 25-hydroxyvitamin D and parathyroid hormone concentration in assessing vitamin D deficiency in pet rabbits

Abstract: Background Vitamin D deficiency and related metabolic bone diseases in pet rabbits have been intermittently debated. In human research, the parathyroid hormone concentration in relation to the 25-hydroxyvitamin D concentration is used to determine vitamin D deficiency. Thus, this study aimed to identify the breakpoint in the 25-hydroxyvitamin D concentration indicating a significant change in the parathyroid hormone concentration in 139 pet rabbits. An enzyme immunoassay kit was used for 25-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Previously, 25(OH)D concentration of 17 ng/mL was suggested as a threshold for vitamin D deficiency in rabbits [ 11 ]. Using this benchmark, all wild rabbits in our study appeared to have severe vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, 25(OH)D concentration of 17 ng/mL was suggested as a threshold for vitamin D deficiency in rabbits [ 11 ]. Using this benchmark, all wild rabbits in our study appeared to have severe vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that one-third of pet rabbits had serum 25(OH)D below the suggested vitamin D deficiency threshold of 17 ng/ml [ 11 ]. The main vitamin D source of pet rabbits was the diet, and outdoor access was not associated with the 25(OH)D concentrations [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies before ours have also demonstrated that VitD de ciency increases glomerulosclerosis and relative interstitial area, and impairs renal function in the progression to CKD after ischemia/reperfusion (I/R) and in the 5/6 nephrectomized rats [28,36]. Studies suggest that these alterations occur due to a lower VDR modulation [37], local overactivation of the renin-angiotensin system (RAS) [22,31,38] and/or secondary factors such as elevated PTH levels in VitD de ciency [39]. However, the mechanisms by which VitD de ciency contributes to the worsening of these changes, mainly in DKD, should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the 25(OH)D concentration, which begins to climb or no longer falls as the PTH concentration lowers, may indicate Vitamin D inadequacy. [19] PTH is elevated when calcium levels are low, or phosphate levels are high. High levels of parathyroid hormone damage bones and cause phosphate and calcium levels in the bones to fluctuate.…”
Section: Discussionmentioning
confidence: 99%